Analisis Komparatif Permainan Tradisional dan Permainan Modern dalam Stimulasi Motorik Kasar Anak Usia Dini: Studi Literatur - Riswandi, Fitta Nurisma (Indonesian Journal of Humanities and Social Sciences, 2024)
Gross motor skills are an important aspect of early childhood development because they form the basis for physical, social, and emotional abilities in later stages. Games, both traditional and modern, are believed to contribute significantly to stimulating these abilities. This article aims to conceptually examine the role of traditional and modern games in supporting gross motor stimulation in early childhood. This research uses a literature study by reviewing ten scientific articles published in 2025. The analysis was conducted descriptively by identifying the main findings from each source and synthesizing them to obtain a comprehensive understanding. The results of the study show that both types of games play a positive role in training children's balance, coordination, agility, and large muscle strength. Traditional games excel in strengthening cultural values, social interaction, and the use of simple media, while modern games excel in visual innovation, interactive features, and technology-based learning motivation. In conclusion, the integration of traditional and modern games can be a creative, adaptive, and contextual learning strategy in the digital age. These findings are expected to contribute theoretically to the development of gross motor stimulation methods in early childhood education institutions.